Engagement strategy has seen FTA's research and recommendations inform the gender-responsive design and implementation of global policy processes - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
FTA recommendations shape the design and implementation of global policy processes. The program's gender research has influenced the design of policy documents produced in the negotiation processes in the Convention on Biological Diversity (CBD), and FTA recommendations on gender indicators for SDG13 on climate change were incorporated in the "Equal Measures 2030" global report